New isolates of Trichoderma spp. as biocontrol and plant growth–promoting agents in the pathosystem Pyrenophora teres-barley in Argentina - Moya, Paulina (2020)
The fungus Pyrenophora teres, causal agent of net blotch of barley, generates important yield losses, mainly regarding grain weight and quality of malt extract for beer production. In order to find new strategies to manage this disease, we evaluated in vitro and in vivo antagonistic interactions among different native isolates of Trichoderma spp. and P. teres. The microorganisms were isolated from different barley crop areas of Buenos Aires province and identified according to morphological features and molecular techniques. Dual cultures were conducted to assess in vitro antagonism using direct interactions. Assays under greenhouse conditions were carried out to evaluate the efficiency of Trichoderma spp. as biocontrol and plant growth–promoting agent. In vitro, all Trichoderma spp. isolates inhibited mycelial growth of P. teres in an 18%–54% range compared to the controls. Microscopic observations of interaction zones revealed morphological alterations of P. teres such as vacuolated mycelium without typical pigmentation and coiling. In vivo, all Trichoderma isolates significantly decreased the incidence of P. teres, up to 55% on barley seedlings. Severity decreased up to 77% on stems and up to 70% on leaves. Likewise, regarding growth–promoting parameters, aerial and radicular dry weight of plants treated with Trichoderma spp. increased up to 20% and 15%, respectively. On the other hand, an increase of chlorophyll (SPAD) of up to 9% compared to the control was recorded in seedlings treated with Trichoderma.